Proceedings of the 50th ACM Technical Symposium on Computer Science Education 2019
DOI: 10.1145/3287324.3287359
|View full text |Cite
|
Sign up to set email alerts
|

What to Expect and What to Focus on in SQL Query Teaching

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 8 publications
9
33
0
3
Order By: Relevance
“…SQL as a language and the formulation of SQL queries can be complex for novices. Several studies have reported about the types of mistakes and errors students encounter when learning to write SQL [3,4,9,37,41,42]. Performance in writing SQL is also linked with students' course performance [2].…”
Section: Learning and Teaching Sqlmentioning
confidence: 99%
“…SQL as a language and the formulation of SQL queries can be complex for novices. Several studies have reported about the types of mistakes and errors students encounter when learning to write SQL [3,4,9,37,41,42]. Performance in writing SQL is also linked with students' course performance [2].…”
Section: Learning and Teaching Sqlmentioning
confidence: 99%
“…Our custom tool allowed passive collection of detailed data that would have been impossible to gather via surveys or similar instruments. We used these data to expand upon previous work devoted to the study of common semantic errors in SQL conducted by Brass and Goldberg [4], as well as studies of SQL learning by Taipalus et al [36] [35] and Ahadi et al [2]. We confirmed the completeness and accuracy of previously-compiled lists of common errors within the context of an undergraduate database course.…”
Section: Casessupporting
confidence: 67%
“…Comparing our results to a similar study of "persistent" errors by Taipalus et al. [35], in which the authors identified types of errors likely to remain unfixed throughout the problem-solving process, we find that our summary results gener- we studied only 375 terminal queries compared to 8,773 final queries analyzed in the Taipalus study. Continued data gathering and study of persistent errors, and the steps leading up to these errors, will likely yield useful insight.…”
Section: Terminal Attemptssupporting
confidence: 64%
“…Students learn bad design practices which later need to be unlearned, the database is subject to anomalies [38], and requires more disk space due to redundancy. Finally, it is not clear whether students should strive for fewer errors, (although other database end-users arguably should), as errors are arguably an efficient way through which students learn, as argued in SQL education research [54,100] as well as broader educational contexts [74].…”
Section: Na7mentioning
confidence: 99%
“…Teaching approaches or considerations regarding student errors SE10 Among queries requiring the use of aggregate functions, illegal or insufficient grouping is the the most frequent type of error [PS02, PS79], followed by the use incorrect functions, incorrect columns as function parameters, missing DISTINCT from the function parameter, and DISTINCT as a function parameter where not applicable[PS79]. SE11 Syntax errors are the cause of failure particularly in queries involving GROUP BY and HAVING clauses, as well as NATURAL JOIN [PS02].…”
mentioning
confidence: 99%